2013
DOI: 10.3389/fendo.2013.00136
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Based Indicators of Insulin Resistance and Metabolic Syndrome in Bottlenose Dolphins (Tursiops truncatus)

Abstract: Similar to people with metabolic syndrome, bottlenose dolphins (Tursiops truncatus) can have a sustained postprandial hyperglycemia and hyperinsulinemia, dyslipidemia, and fatty liver disease. A panel of potential postprandial blood-based indicators of insulin resistance and metabolic syndrome were compared among 34 managed collection dolphins in San Diego Bay, CA, USA (Group A) and 16 wild, free-ranging dolphins in Sarasota Bay, FL, USA (Group B). Compared to Group B, Group A had higher insulin (2.1 ± 2.5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 47 publications
3
53
0
Order By: Relevance
“…Because overexpression of OGT has been associated with insulin resistance and dyslipidemia in mice (Yang et al. 2008), expansion of OGT (11 copies) in the bottlenose dolphin genome may be underlying the unusual response of this species to insulin (Venn-Watson et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because overexpression of OGT has been associated with insulin resistance and dyslipidemia in mice (Yang et al. 2008), expansion of OGT (11 copies) in the bottlenose dolphin genome may be underlying the unusual response of this species to insulin (Venn-Watson et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Other features reported in cetaceans include extreme longevity (>200 years in the case of the bowhead whale, Balaena mysticetus ; George et al. 1999; George and Bockstoce 2008), reduced cancer incidence (e.g., in the blue whale, Balaenoptera musculus ; Caulin and Maley 2011), and resistance to insulin (bottlenose dolphin, Tursiops truncatus ; Venn-Watson et al. 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The insulin sensitizing action of adiponectin is impressively conserved among mammals, extending from mice and humans (Turer and Scherer, 2012) to the yellow-bellied marmot and dolphin (Florant et al, 2004; Venn-Watson et al, 2013). While the insulin sensitizing effects are a combination of the vast metabolic effects exerted on multiple tissues, adiponectin also acts locally on the adipocyte to increase glucose uptake, contributing to euglycemia and promotion of adipose tissue expansion.…”
Section: Adipocyte Communication Maintains Systemic Glucose Homeostasismentioning
confidence: 99%
“…Serum ferritin levels, hepatic function, age, sex, alcohol consumption, and hepatitis C can all affect the development of the clinical syndrome (Rochette et al 2010). Managed-collection bottlenose dolphins have significantly higher iron levels than free-ranging dolphins, indicating that environmental, dietary, and metabolic factors likely play significant roles in disease development (Mazzaro et al 2012;Venn-Watson et al 2013).…”
mentioning
confidence: 99%
“…Bottlenose dolphins have a diabetes-like metabolism, including a sustained postprandial hyperglycemia (Venn-Watson et al 2007). Subsequent studies have demonstrated an association between elevated insulin levels and elevated serum iron and hemochromatosis in dolphins (Venn-Watson et al 2011, 2013. Further studies are needed to assess potential parallels between insulin resistance-associated hemochromatosis in dolphins and humans.…”
mentioning
confidence: 99%